Analisis Pembelajaran Seni Musik pada Materi Ritme di SD Sukaratu - Annisa Nabila; Resa Respati (YASIN, 2026)
Although music arts learning has received attention in several previous studies, research specifically discussing rhythm learning in elementary schools remains limited, particularly regarding the implementation of learning and teachers’ needs in teaching rhythm material. This study aimed to analyze the implementation of music arts learning on rhythm material in elementary schools. This study used a descriptive qualitative approach. Data were collected through semi-structured interviews, observation, and documentation studies, with the research subjects consisting of classroom teachers who were directly involved in SBdP learning, particularly music arts material. The results showed that music arts learning had not been implemented optimally, especially in the teaching of rhythm. Teachers had not explicitly taught rhythm concepts, such as beat patterns, tempo, and rhythmic patterns. In addition, several obstacles were found, including teachers’ limited understanding of rhythm and the unavailability of a systematic rhythm teaching module. These findings are in line with social constructivist theory and Howard Gardner’s theory of musical intelligence, which emphasize the importance of active and meaningful musical experiences in the learning process. The conclusion of this study emphasizes the need to develop a rhythm teaching module that is aligned with the characteristics of elementary school students and teachers’ needs in music arts learning. The implications of this study include enriching studies on music learning in elementary schools and recommending the development of more innovative and contextual rhythm learning tools. This study also opens opportunities for further research on the implementation and effectiveness of rhythm teaching modules in elementary schools.